2014
DOI: 10.4236/ajac.2014.511078
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermal Properties of Tb, Ce Doped Y<sub>2.97</sub>Gd<sub>0.03</sub>Al<sub>2</sub>Ga<sub>3</sub>O<sub>12</sub> Single Crystals

Abstract: The structural and thermal properties of yttrium-aluminum-gadolinium-gallium (Y 2.97 Gd 0.03 Al 2 Ga 3 O 12 ) single crystals doped with terbium (0.1%), cerium (0.01%) and co-doped with both terbium and cerium ((0.1, 0.01)%) were investigated. All samples were heated (calcined) at 1400˚C for 15 hours before crystallization. X-ray powder diffraction (XRD) patterns of all calcined samples showed the presence of yttrium gallium aluminate (Y 3 Al 2 Ga 3 O 12 ) and gadolinium gallium oxide (Gd 3 GaO 6 ) while the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…White LEDs, based on blue LED chips (have been deve− loped since 1991, first time by Nichia Co.) coated with yel− low emitting phosphor were first reported in 1996, and Ce 3+ doped YAG phosphor, with the general formula: Ce:YAG has been available since 1960s, but the YAG:Ce is considered a cool phosphor, due to the lack of the red com− ponent [5][6][7][8][9]. In the last years, the research is turning to co−doping the YAG:Ce, in order to shift the emission spec− trum by partially substituting the Y or Al cations with differ− ent ions.…”
Section: Introductionmentioning
confidence: 99%
“…White LEDs, based on blue LED chips (have been deve− loped since 1991, first time by Nichia Co.) coated with yel− low emitting phosphor were first reported in 1996, and Ce 3+ doped YAG phosphor, with the general formula: Ce:YAG has been available since 1960s, but the YAG:Ce is considered a cool phosphor, due to the lack of the red com− ponent [5][6][7][8][9]. In the last years, the research is turning to co−doping the YAG:Ce, in order to shift the emission spec− trum by partially substituting the Y or Al cations with differ− ent ions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated the necessity of these studies by investigating the structural and thermal properties of Tb, Ce doped Y 3 Al 5 O 12 (YAG) single crystals. 13,14 The results act as pointers to the research that needs to be undertaken in parallel to both develop radical designs of LDIL modules and the associated single crystals used as emitting targets. In this report we have focused on studying different crystal sizes of the same phosphor material with the same LDs.…”
mentioning
confidence: 96%